A synchrotron radiation study of high-lying excited states of matrix-isolated atomic magnesium: Low-Temperature Physics and Chemistry in Cryomatrice - Kerins, Paul; Healy, Brendan; McCaffrey, John G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
Previous steady-state and time-resolved luminescence spectroscopy of 3p 1P1 atomic magnesium, isolated in thin film samples of the solid rare gases, has been extended to include the higher energy 4p 1P1 excitation. Well resolved site splittings have been recorded in Mg/Ar samples for excitation tothe 4p 1P1 level. A small red shift in the absorption energy to the 4p 1P1 level for Mg/Ar contrasts witha small blue shift on absorption to the 3p 1P1 level. Direct emission from the 4p 1P1 level is not observed in any of the rare gas matrices, instead intense emission from the low energy 3p 1P1 level is. Measurements of the emission decay curves in Mg/Ar have revealed slow rates in the steps feeding the 3p 1P1 level following 4p 1P1 excitation. The reason for the differential shifting of the 4 p 1P1 and 3p 1P1 levels as well as the lack of direct 4p 1P1 emission is thought to be related to the strong binding interaction between Mg in the 4p 1P1 state and the rare gases.